TRANSFORMASI KURIKULUM PENDIDIKAN DASAR DAN MENENGAH DI INDONESIA - Andi Prastowo (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The curriculum is ideally adaptive to the development of science and technology. The aim is that the outcomes of education have capabilities that are relevant to user needs and the challenges of the times. Curriculum transformation is a common thing in various countries, one of which is Indonesia. However, starting in 2015, the curriculum and madrasah curriculum transformation in Indonesia was implemented by implementing two curricula at once, namely the 2013 curriculum and the Education Unit Level Curriculum (EULC). This is rare in previous times. Departing from this issue, this article attempts to uncover the background and strategies and the problems faced in implementing the transformation of the primary and secondary education curriculum in Indonesia towards a dual curriculum. The research method used in this study is literature study. The findings of this study indicate that the transformation or changes in curriculum in Indonesia from EULC to the 2013 curriculum, then the dual curriculum is due to the low quality of national education. The application of dual curriculum has been implemented since 2015 using the 2013 curriculum and EULC at the same time for all primary and secondary education levels. This policy was carried out due to various technical issues in the 2013 curriculum implementation.